Discovery of Jet–Bubble–Disk Interaction: Jet Feedback on a Protoplanetary Disk Via an Expanding Bubble in WSB 52 - Masataka Aizawa; Ryuta Orihara; Munetake Momose (The Astrophysical Journal)
While stellar jets and outflows are fueled by accretion from disks, their direct influence on disks remain unexplored. Here, we revisit Atacama Large Millimeter/submillimeter Array observations of ^12 CO ( J  = 2–1) line emission for the young stellar object WSB 52. We identify an expanding bubble that interacts with its protoplanetary disk. Given that the disk axis points toward the bubble’s center and the kinetic energy of the bubble is roughly 10 ^41 erg, we postulate that stellar jets, aligned with the disk axis, have triggered the bubble. The bubble morphology is consistent with uniform expansion with partial concavity, implying the bubble-disk interaction. Correspondingly, the shape and the velocity field of protoplanetary disk appear to be deformed and exhibit high-velocity components, suggesting strong interactions and mass loss from the disk. The discovery of jet feedback onto the disk via the bubble—which we term the jet-bubble-diskjet–bubble–disk interaction—sheds new light on the dynamical processes governing star and planet formation.